A DISCOURSE ANALYSIS OF ENGLISH TEXTS INTRODUCING SPORTSWEAR PRODUCTS - Nguyễn Thị Thùy Ngân (Trường Đại học Ngoại ngữ, 2025)
This study aims at conducting a discourse analysis of texts introducing sportswear products in English. The data for analysis in this thesis are 100 samples of texts introducing sportswear products in English collected from websites of companies manufacturing sportswear products in the United States, the United Kingdom and in Australia. The study is carried out based on the theories of discourse analysis and a combination of a variety of methods such as descriptive, comparative, contrastive, analytic and inductive. The study focuses on analyzing some typical discourse features in order to point out the outstanding characteristics of texts introducing sportswear products in English in terms of their layout, lexical features, syntactic features and cohesive devices. The findings of this study are clearly presented based on a survey of 100 English texts introducing sportswear products (ETSPs). Hopefully, the results of the study will really provide some practical applications for teaching and learning English. This study may also be useful for those who are interested in texts, specially of texts introducing sportswear products in English